2014
DOI: 10.1002/ijc.29162
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized [1,3‐13C2]ethyl acetoacetate is a novel diagnostic metabolic marker of liver cancer

Abstract: An increased prevalence of liver diseases such as hepatitis C and nonalcoholic fatty liver results in an augmented incidence of the most common form of liver cancer, hepatocellular carcinoma (HCC). HCC is most often found in the cirrhotic liver and it can therefore be challenging to rely on anatomical information alone when diagnosing HCC. Valuable information on specific cellular metabolism can be obtained with high sensitivity thanks to an emerging magnetic resonance (MR) technique that uses 13 C labeled hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…HP 13 C‐AcAc was first reported as an imaging probe by Jensen et al In that study, ethyl [1,3‐ 13 C]AcAc was used as a marker for decreased esterase activity in liver tumors but HP‐β‐HB was not detected. Recently, Miller et al investigated the metabolism of HP‐[1‐ 13 C]AcAc and HP[1‐ 13 C]β‐HB in isolated, perfused rat hearts as well as in vivo .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…HP 13 C‐AcAc was first reported as an imaging probe by Jensen et al In that study, ethyl [1,3‐ 13 C]AcAc was used as a marker for decreased esterase activity in liver tumors but HP‐β‐HB was not detected. Recently, Miller et al investigated the metabolism of HP‐[1‐ 13 C]AcAc and HP[1‐ 13 C]β‐HB in isolated, perfused rat hearts as well as in vivo .…”
Section: Discussionmentioning
confidence: 55%
“…HP 13 C-AcAc was first reported as an imaging probe by Jensen et al 43 In that study, ethyl [1,[3][4][5][6][7][8][9][10][11][12][13] 44 This study demonstrated that metabolism of HP 13 C-ketones can be detected in the heart, and several downstream metabolites of the HP 13 C-agents were observed. We first reported with preliminary results that it is possible to correlate altered mitochondrial redox in perfused rat hearts with the production of HP-β-HB from HP-AcAc.…”
Section: Discussionmentioning
confidence: 86%
“…A small reagent impurity, ethyl‐[1‐ 13 C]acetoacetate, was visible in the batch of synthesized [1‐ 13 C]acetoacetate used for ex vivo experiments. Owing to the reported subsequent hepatic metabolism of ethyl‐[1‐ 13 C]acetoacetate to ethanol and [1‐ 13 C]acetoacetate, the presence of this impurity ex vivo was not considered to be significant for subsequent in vivo translation.…”
Section: Resultsmentioning
confidence: 99%
“…CE catalyzes phase I metabolism and a hydrolytic reaction by CE is used as an activation mechanism of several prodrugs2324. Therefore, CE has been an attractive target of hyperpolarized MR molecular sensors25.…”
Section: Resultsmentioning
confidence: 99%